Liver description in three neotropical anuran species: from anatomy to ultrastructure - Fanali, Lara Zácari [UNESP]; Freitas, Juliane Silberschmidt; Franco-Belussi, Lilian; Taboga, Sebastião Roberto [UNESP]; de Oliveira, Classius [UNESP] (Wiley, 2021)
The liver is a well-defined organ regarding its functions; however, it may present morphological variations among species. Since anurans may be exposed to toxic substances in their environment, which can disrupt liver's morphology and function, descriptive studies of organs are important to be carried out under natural condition. Thus, this study aimed to describe morphological aspects of liver in three Neotropical anuran species commonly used as experimental models: Physalaemus cuvieri (Leptodactylidae), Leptodactylus fuscus (Leptodactylidae) and Rhinella diptycha (Bufonidae). Anatomical, histological and ultrastructural analyses of six male samples of each species were carried out. A restricted analysis of the three species showed that livers' anatomy and ultrastructure are quite similar—they present three lobes, rounded nucleus polyhedral hepatocytes and some glycogen contents; however, histologically, there was a difference in the structural arrangements. In R. diptycha the parenchyma was arranged in a single cord, whereas in P. cuvieri and L. fuscus, there were double ones. This parenchyma structuring is highly variable considering Amphibia class. Knowledge about hepatic morphology and ultrastructure in amphibians is a key measure to detect changes in experimental studies and to infer about possible physiological and / or metabolic changes, when these animals are exposed to adverse conditions.
Keywords: amphibians; hepatic cord; hepatocyte; histology